(untitled) (TEL Tempo, Espaço e Linguagem, 2026)
This article provides a historical analysis of the criminal case of the minor Raymundo (1937) in Paraná, Brazil, to investigate how the judiciary discursively produced the figure of the "abnormal minor". Through the examination of court records, the article analyzes the role of the juvenile judge in mobilizing legal and medical knowledge, guided by the 1927 Minor’s Code. Among other issues, the study shows how criminal law discourse practices manufactured juvenile abnormality as a justification for social exclusion measures.